El fuego : (diario de una escuadra) - Barbusse, Henri, 1873-1935 (Ediciones de Intervención Cultural/Montesinos, 2009)
"Under Fire follows the fortunes of the French Sixth Battalion during the First World War. For this group of ordinary men, thrown together from various regions of France and all longing for home, war is simply a matter of survival: the arrival of their rations, a glimpse of a pretty girl, or a brief reprieve in the hospital is all they can hope for. Based on his own experience of the Great War, Henri Barbusse's novel is a powerful account of one of the greatest horrors mankind has inflicted on itself. For the group of ordinary men in the French Sixth Battalion, thrown together from all over France and longing for home, war is simply a matter of survival, lightened only by the arrival of their rations or a glimpse of a pretty girl or a brief reprieve in the hospital".